Evaluation of Soil Properties of the Alluvial Landform in Three Locations of Donggala Regency, Central Sulawesi - . HIKMATULLAH; . SUKARMAN (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2007)
Alluvial landforms in Donggala Regency, Central Sulawesi, are main agricultural land, but information of soil properties has not been yet studied and published. The objectives of the study were to evaluate soil physical, chemical and mineralogical properties of alluvial landform and potential fertility for agriculture. Five pedons from Palu valley, five pedons from northcoast and three pedons from west coast of Donggala regency were selected for laboratory analyses. The pedons represent dominant soil groups, consisting of Ustifluvents, Haplustepts, Eutrudepts, and Endaoquepts. To evaluate soil property differences among the locations, a paired test comparison was applied. To compare clay or organic carbon contents with CEC soils, a multiple linier regression was applied. The results indicatethat the soils of the areas have loamy sand to sandy clay loam textures, slightly acid to slightly alkaline, low to very low organic carbon contents, high P2O5 and K2O (extracted by HCl 25%) contents, medium to high available P2O5 (extracted by Olsen), low soil CEC, high clay CEC and base saturation. The soil properties showed wide variation with coefficient variation (CV) ranging from 23 to 98%, except for pH and base saturation (CV<20%). The results of pair test comparison indicated that sand content, total K2O, and available P2O5 were differ very significantly for all pairs, whereas clay, silt, and organic carbon contents, CEC soil and CEC clay were differ very significantly only for two pairs of the locations that was between Palu vallley and north coast and west coast. The results of multiple linierregression analyses show that clay content has closer relationship to CEC soil rather than organic carbon content. Composition of sand mineral fraction was dominated by quartz and rock fragments, but it shows relatively high weatherable minerals (12-46%), while clay mineral was a mixture of smectite and illite. The potential fertility of the soils was relatively good,with main contraints of low organic matters and low soil CEC. Incorporation of organic matters, such as green manure and crop residues, is suggested to improve and increase CEC soils and nutrient availability.